Green Bonds, Conventional Bonds and Geopolitical Risk - Lisa Sheenan (Queen's University Belfast, Queen's Business School, 2023)
This paper analyses linkages between green, conventional (corporate and sovereign) bond markets and geopolitical risk in high and low volatility periods between 2014 and 2022 using a Markov-switching VAR (MS-VAR) framework. The results indicate that geopolitical risk significantly affects green bonds in periods of high volatility, but does not do so to conventional bond markets. Green bond markets are significantly affected by sovereign and corporate bonds in both regimes, with stronger effects from corporate bonds evident in high volatility periods. This suggests that green bonds behave differently to conventional bonds and may be more susceptible to geopolitical risk and contagion.
Keywords: G10; G11; C34; 330; Green bonds; Geopolitical Risk; Markov Switching